2020
DOI: 10.12688/f1000research.25901.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental risk factors on delirium and benefits of noise and light modifications: a scoping review

Abstract: Background: To explore existing literature on the association between environmental risk factors and delirium, and to investigate the effectiveness of environmental modifications on prevention or management of delirium. Methods: This is a scoping review of peer-reviewed studies in PubMed and the reference lists of reviewed articles. Observational studies reporting the effect of noise, light, and circadian rhythm on delirium and interventional studies assessing delirium in modified environments were reviewed. R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 90 publications
0
1
0
2
Order By: Relevance
“…The present study compared window-side beds with non-window-side beds in identical layout rooms of a single center, which was considered to assess the direct impact of windows on delirium through sunlight exposure and visibility of the outside world. Indeed, almost half of the ICU research reported that windows did not decrease the development of delirium ( 42 ), implying the possibility that the simple presence of a window did not associate with delirium prevention. Furthermore, any significant associations for window-side beds were not compared with delirium in subgroup analyses factoring the environments of patients or rooms.…”
Section: Discussionmentioning
confidence: 99%
“…The present study compared window-side beds with non-window-side beds in identical layout rooms of a single center, which was considered to assess the direct impact of windows on delirium through sunlight exposure and visibility of the outside world. Indeed, almost half of the ICU research reported that windows did not decrease the development of delirium ( 42 ), implying the possibility that the simple presence of a window did not associate with delirium prevention. Furthermore, any significant associations for window-side beds were not compared with delirium in subgroup analyses factoring the environments of patients or rooms.…”
Section: Discussionmentioning
confidence: 99%
“…Patienten mit Delir weisen oft pathologische Melatoninspiegel auf, unabhängig vom Alter [34,35]. Dies legt die Hypothese nahe, dass adäquate Lichtbedingungen, oder gar eine gezielte Lichtintervention, zur Prävention und Therapie des Delirs beitragen können.…”
Section: Merkeunclassified
“…Modifikationen der Umgebungsfaktoren in dem oben erwähnten innovativen Raumkonzept von Luetz et al an der Charité[37] umfassten neben der beschriebenen Lichtdecke den Umbau der Patientenzimmer mit einem abgetrennten Beobachtungsraum für Personal sowie die Abtrennung des Beatmungsgeräts und Infusionspumpen durch eine schallschützende Holzwand zur Lärmreduktion und Abschirmung. In einem Scoping Review zum Thema Designinterventionen im Delir-Management wird bei insgesamt bisher schwacher Evidenzlage ein möglicher Vorteil für die Etablierung von Ruhezeiten-Protokollen, Ohrstöpseln und Exposition mit hellem Licht zum Management des Delirs gesehen[35].Zusammenfassend lassen sich aus der aktuellen Evidenzlage noch keine definitiven Schlüsse über die Art, Wirksamkeit und Kosteneffektivität von Designinterventionen außerhalb von Multikomponentenmaßnahmen zum Management des postoperativen Delirs ableiten. Dies kann jedoch Gegenstand zukünftiger Forschung sein, um Risikofaktoren für die Entwicklung eines postoperativen Delirs im Krankenhaus der Zukunft zu minimieren.…”
unclassified